The call of the wild - London, Jack (Oxford University Press, 2000)
When men find gold in the frozen north of Canada, they need dogs - big, strong dogs to pull the sledges on the long journeys to and from the gold mines. Buck is stolen from his home in the south and sold as a sledge-dog. He has to learn a new way of life - how to work in harness, how to stay alive in the ice and the snow ...and how to fight. Because when a dog falls down in a fight, he never gets up again